THE EFFECTIVENESS OF USING POP-UP BOOK ON STUDENTS’ MOTIVATION IN LEARNING ENGLISH SUBJECT AT SEVENTH GRADE OF SMP N 6 BATHIN SOLAPAN - Deny Silvia; Zulfia Siskawati; Khusnul Khotimah (Program Studi Pendidikan Bahasa Inggris, 2025)
Learning English as a foreign language plays a crucial role in supporting students’ academic development and global communication skills. However, many junior high school students still face low motivation in learning English, which hinders their ability to achieve optimal learning outcomes. Previous studies have shown that innovative media such as pop-up books can improve students’ engagement, yet research focusing on their effectiveness in motivating students in rural schools remains limited. This study aims to investigate the effectiveness of using pop-up books on students’ motivation in learning English at the seventh grade of SMP N 6 Bathin Solapan. This study was quantitative with survey research design. Measurement of the effectiveness of the using Pop-Up book on students’ motivation in learning English subject is calculated through correlation analysis, hypothesis testing and effective testing. The findings revealed that the using Pop-Up book on students’ motivation in learning English subject at seventh grade of SMP N 6 Bathin Solapan is effective. In conclusion, the use of pop-up books is proven to be effective in enhancing students’ motivation in learning English. The study suggests that English teachers, particularly in junior high schools, should consider integrating pop-up books and similar interactive media as alternative teaching strategies to foster a more motivating and engaging learning environment.